2016
DOI: 10.1002/btm2.10018
|View full text |Cite
|
Sign up to set email alerts
|

Reducing neuroinflammation by delivery of IL‐10 encoding lentivirus from multiple‐channel bridges

Abstract: The spinal cord is unable to regenerate after injury largely due to growth‐inhibition by an inflammatory response to the injury that fails to resolve, resulting in secondary damage and cell death. An approach that prevents inhibition by attenuating the inflammatory response and promoting its resolution through the transition of macrophages to anti‐inflammatory phenotypes is essential for the creation of a growth permissive microenvironment. Viral gene delivery to induce the expression of anti‐inflammatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 105 publications
(263 reference statements)
6
61
1
Order By: Relevance
“…However, we also found that the number of p57kip2 suppressed cells was severely reduced upon grafting into lesioned CNS tissue suggesting that a promoted oligodendroglial fate acquisition on the one hand facilitates successful tissue integration but on the other hand might come with an increased sensitivity toward hostile cues as described before (Casha, Yu, & Fehlings, ; Crowe, Bresnahan, Shuman, Masters, & Beattie, ; Pfeifer et al, ; Rowland, Hawryluk, Kwon, & Fehlings, ; Vroemen, Aigner, Winkler, & Weidner, ). An influence of spinal cord infiltrating peripheral immune cells (Anderson, ; Margul et al, ) can also not be excluded yet. Such an impact could only be addressed by future transplantation experiments into subacute spinal cord injuries at later time points featuring reduced inflammation and beyond secondary cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also found that the number of p57kip2 suppressed cells was severely reduced upon grafting into lesioned CNS tissue suggesting that a promoted oligodendroglial fate acquisition on the one hand facilitates successful tissue integration but on the other hand might come with an increased sensitivity toward hostile cues as described before (Casha, Yu, & Fehlings, ; Crowe, Bresnahan, Shuman, Masters, & Beattie, ; Pfeifer et al, ; Rowland, Hawryluk, Kwon, & Fehlings, ; Vroemen, Aigner, Winkler, & Weidner, ). An influence of spinal cord infiltrating peripheral immune cells (Anderson, ; Margul et al, ) can also not be excluded yet. Such an impact could only be addressed by future transplantation experiments into subacute spinal cord injuries at later time points featuring reduced inflammation and beyond secondary cell death.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐10 has been demonstrated to promote functional recovery in SCI models in rats66, 67, 68, 69, 72, 73, 74 and mice 58, 64, 65, 70, 71. IL‐10 affects inflammation through regulation of activation of microglia/macrophages70, 71 and astrocytes,72 as well as reducing the production of TNF‐α,72, 73 IL‐1β, S100β, and inducible nitric oxide synthase (iNOS) 65.…”
Section: Roles Of Inflammatory Cytokines In Sci Repairmentioning
confidence: 99%
“…Local applications of lentivirus‐mediated regulation of both TNF‐α228 and IL‐1071 promoted functional recovery. In addition to inflammatory cytokines, local lentivirus‐mediated regulation of other proteins also affected inflammation and facilitated neurorepair.…”
Section: Local Delivery Of Therapeutic Agents Regulates Inflammatory mentioning
confidence: 99%
“…In this context, biomaterials may be used as platforms to deliver factors specific to reduce the immune response and to minimize the role of the injury and inflammatory response on organoid engraftment. [133,134] Collectively, biomaterial systems have the potential to recapitulate the physical and chemical properties of the native organ in order to maintain and mature organoid models of the respiratory and digestive systems. [18,21,129] Creating an environment with the necessary properties for tissue maintenance and maturation will allow for further manipulation to enhance organoid growth and maturation in vitro, or may promote specific structures and engraftment in vivo.…”
Section: Alveolar Organoidsmentioning
confidence: 99%